2002
DOI: 10.7326/0003-4819-136-8-200204160-00008
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hepatotoxicity Associated with the Dietary Supplement LipoKinetix

Abstract: The use of LipoKinetix may be associated with hepatotoxicity. Despite extensive evaluations, no other cause for hepatotoxicity could be identified in the seven patients studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(107 citation statements)
references
References 12 publications
1
101
1
3
Order By: Relevance
“…1,7,8,12,22,23 In contrast, the current (+)-UA feeding study in sheep suggests a primary myotoxic effect in ruminants. This discrepancy is not surprising considering the differences in monogastric versus ruminant physiology.…”
Section: Discussioncontrasting
confidence: 72%
“…1,7,8,12,22,23 In contrast, the current (+)-UA feeding study in sheep suggests a primary myotoxic effect in ruminants. This discrepancy is not surprising considering the differences in monogastric versus ruminant physiology.…”
Section: Discussioncontrasting
confidence: 72%
“…For instance, usnic acid, a dietary supplement promoted for weight loss, was linked to 21 reported cases of hepatotoxicity, seven of which resulted in complete liver failure (Favreau et al, 2002;Frankos, 2005). As such, the FDA issued a warning against using supplements containing usnic acid.…”
Section: Discussionmentioning
confidence: 99%
“…49 In two models of inflammation "an acute rat paw edema and a chronic rat cotton pellet with 100 mg/kg oral dose", the antiinflammatory action of (+)-UA was similar to ibuprofen with a similar dose. 50 Another study reported that usnic acid protects lipopolysaccharide produced mice acute lung injury by alleviating the inflammatory reactions and oxidative stress. Assessment of the anti-inflammat o ry action showed that usnic acid mitigated the expression of: "tumor necrosis factor alpha (TNF-a), interleukin-6 (IL-6), interleukin-8 (IL-8) and macrophage inflammat o ry protein-2 (MIP-2)".…”
Section: Usnic Acid As Antiinflmmatory Agentmentioning
confidence: 99%